2023
DOI: 10.1055/a-2045-8122
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Patient-Reported Outcomes and Complications of Pedicled Latissimus Flap Breast Reconstruction

Abstract: Background: The latissimus dorsi (LD) flap is a reliable option for breast reconstruction. This is particularly true in patients with contraindications to abdominally based autologous breast reconstruction. A systematic review of patient satisfaction and health related quality of life following LD breast reconstruction using the BREAST-Q survey was conducted. The scope of the review was to determine the degree of patient satisfaction following the procedure and to examine how patient satisfaction from the ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In our series, none of the patients experienced total or partial flap necrosis. In a recent systematic review of pedicled LD breast reconstruction, Peshel et al reported a low rate of flap necrosis (partial or total) of 4% [20]. Similarly, in a large cohort of 208 patients, Wattoo et al reported a flap loss rate of 3.4% [21].…”
Section: Discussionmentioning
confidence: 98%
“…In our series, none of the patients experienced total or partial flap necrosis. In a recent systematic review of pedicled LD breast reconstruction, Peshel et al reported a low rate of flap necrosis (partial or total) of 4% [20]. Similarly, in a large cohort of 208 patients, Wattoo et al reported a flap loss rate of 3.4% [21].…”
Section: Discussionmentioning
confidence: 98%